Ultra-low-cost, crosstalk-free, fast-responding, wide-sensing-range tactile fingertip sensor for smart gloves - Sinha, Anoop Kumar (2022)
Skin-inspired sensors are all the rage in robotic applications. They take inspiration from the human skin's sensory abilities and use their abilities to sense things like temperature and pressure. Herein, fabrication of ultra-low-cost (<$1.5), ultra-thin, wide range, and crosstalk-free skin-inspired tactile sensors is presented. The sensors consist of piezoresistive pressure sensing elements sandwiched between 3D printed silver nanoparticle electrodes on polyimide layers just like the epidermis, dermis, and hypodermis of human skin. The response time of individual sensing nodes is 4 ms which is faster than the response time of the human skin (30–50 ms). The sensors exhibit high sensitivity (1.35 kPa−1), low hysteresis (9.22%), and a wide pressure sensing range (5–600 kPa). The sensor arrays are assembled on the fingertips of a commercial glove to make a smart glove. By combining the sensor information and deep learning, the smart glove is used to identify sharp and blunt objects with a classification accuracy of 95.9% and the direction of applied pressure when touched by an object with a classification accuracy of 97.8%. Furthermore, the smart glove is used to generate pressure maps in real-time while grabbing six different objects handled by humans in daily life.